"RASHOMON EFFECT" AS COMMUNICATIVE DISORIENTATION PHENOMENON (MEDIARESEARCH ESSAY) - H. F. Ovcharenko (Концепт: философия, религия, культура, 2018)
The paper discusses one of the topical problems of present-day Western massmedia studies, namely, the "Rashomon Effect" in Communication. A detailed analysis of this professional difficulty by the Canadian colleagues (in "Canadian Journal of Communication", 2016/No 2) gave us the idea of our own research with the Russian media texts (October 2016 - October 2017). We explain the origins of the term "Rashomon Effect" (named after Kurosawa's film, 1950) and offer brief characteristics of this phenomenon (premeditated / unpremeditated "Rashomon Effect"). Our paper presents the "Rashomon Effect" as a communicative disorientation, one of the "specific difficulties" for journalists and as the complex epistemological problem. The "Rashomon Effect" mechanisms are numerous; however, the starting point of the "Rashomon Effect" is situated on the basis of inadequate information. The research is developed on the base of some debating publications in the Russian media (for example, Ivan the Terrible Monument in Orel, 2016; A. Uchitel's film "Matilda", 2016-2017). Among other things, the keynote "Russian" factor is to look for historical "veritable truth" through the "Rashomon Effect". Finally, the appearance of the film's name for cognitive and cultural phenomenon known in foreign communication, psychology, anthropology, sociology, epistemology, demonstrates that "The Rashomon Effect" has the global character, but it should be noted that Russian media researchers rarely utilize this term. We can conclude that the "Rashomon Effect" is not only about differences of perspectives; it is the result of the journalist unscrupulousness (premeditated "Rashomon Effect") or of the journalist error (unpremeditated "Rashomon Effect"). In our opinion, the question of the "Rashomon Effect" in Russian media needs to be under discussion for the neutralization of this professional problem.